FLEXIBLE DYNAMICS ANALYSIS OF SLEY SYSTEM FOR HIGH-SPEED RAPIER LOOM BASED ON FINITE ELEMENT METHOD - LU ChunHui; JIN GuoGuang; WEI Zhan (Jixie qiangdu)
In view of the insufficient strength,vibration deformation and fracture of the sley system of the beating-up mechanism in the existing loom,the structure of the sley system is optimized. According to the finite element modal calculation theory,the vibration equation of the new multi-degree-of-freedom sley foot system is established. The modal and mode of the sley foot are analyzed in ANSYS. The rigid-flexible coupling model of the new beating-up mechanism is established in ADAMS,and the flexible dynamic simulation and stress analysis are carried out. The results show that the new sley system is easy to manufacture and install,and can meet the requirement of mechanical properties of beating-up motion. The possibility of resonance deformation of the new sley is very small. The beating-up acceleration curve of the flexible sley foot fluctuate more than that of the rigid body,and the change of the loom speed have a great influence on the acceleration of the beating-up mechanism. The stress distribution of the main body of the new sley is less than that of the original sley.